Factors Affecting the Prevention of Covid-19 Transmission in School-Age Children - Astuti, Dyah Dwi; Handayani, Tri Widyastuti; Astuti, Duwi Pudji; Mandawati, Murti (Fakultas Ilmu-ilmu Kesehatan, 2022)
The COVID-19 pandemic has had a physical and psychological impact on school-age children. Parents also have the challenge of shaping the behavior of school-age children regarding the prevention of COVID-19 transmission. This study aims to analyze the factors that influence the behavior of school-age children in preventing the transmission of COVID-19. This is a cross-sectional study with a random sampling technique and distributed a questionnaire survey to parents who have school-age children that are 6-12 years old, and the total was 474 people. The questionnaire assesses school-age children's behavior by applying the Health Belief Model theory. Multiple logistic regression tests found that parental age, parental education level, parental knowledge, and residence had a significant influence on the prevention of COVID-19 transmission in school-age children (P-value < 0.05). Four variables having a chance in good prevention of COVID-19 transmission at school-age children, there were elderly parents had a 5.6-time (95% CI OR 2.8-11.5), parents with higher education had 2.9 times (95% CI OR 1.9:4,3), parents with good knowledge had 2.6-time (95% CI OR 1.7-4.1), urban areas also had 1.86-time (95% CI OR 1.18-2.95). Parental age, parental level education, parental knowledge, and residence have a significant influence on the prevention of COVID-19 transmission behavior in school-age children.